2016
DOI: 10.1177/1054773816683504
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Self-Efficacy Scale: Validation of the Arabic Version Among Jordanians With Chronic Diseases

Abstract: This study assessed the psychometric properties of the Arabic version of Exercise Self-Efficacy scale (ESE-A) among Jordanian outpatients with a variety of chronic diseases using descriptive cross-sectional design. Participants' scores of ESE-A significantly correlated with their reported weekly exercise frequency ( r = .23, p< .001), duration ( r = .31, p< .001), and evaluation of their physical exercise ( r = .39, p< .001). The construct validity was tested using exploratory factor analysis, which retained a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 24 publications
2
29
0
Order By: Relevance
“…However, the original English version of the SE scale was utilised among Australian cardiac patients by Everett et al (25), who reported high internal consistency (α = 0.95) and demonstrated no floor or ceiling effects. Moreover, one SE scale translated to another language, Arabic (26), also showed good internal consistency (α = 0.89).…”
Section: Discussionmentioning
confidence: 92%
“…However, the original English version of the SE scale was utilised among Australian cardiac patients by Everett et al (25), who reported high internal consistency (α = 0.95) and demonstrated no floor or ceiling effects. Moreover, one SE scale translated to another language, Arabic (26), also showed good internal consistency (α = 0.89).…”
Section: Discussionmentioning
confidence: 92%
“…The second category included eleven studies which evaluated the HPM as a mean to predict physical activity (PA) in a sample of Iranian adolescent boys [7], compared perceived self-efficacy, exercise benefits, exercise barriers, and commitment to exercise between patients diagnosed with osteoporosis and osteoarthritis, and assessing the influence of perceived exercise self-efficacy, exercise benefits, and barriers on commitment [8], explored perceived exercise self-efficacy, benefits and barriers, and commitment to exercise among Jordanians with chronic illnesses [14], explored perception of exercise benefits and barriers among Jordanian patients' with End Stage Renal Disease (ESRD) [11], used HPM to provide insight into the relationship between dietary and fluid non-adherence, depressive symptoms, quality of life, perceived barriers and benefits of exercise, and perceived social support among Jordanian patients with ESRD receiving hemodialysis [9], conducted an evaluation of an educational program based on the HPM and stages of change to improve physical activity (PA) behavior among Iranian adolescents [10], used Pender's HPM to describe and identify the predictors of health-promoting behaviors in Nepalese migrant workers in Korea [13], examined the psychometric properties of the Arabic version of Bandura's Exercise Self-Efficacy scale (ESE-A) among Jordanian patients with different chronic diseases [16], assessed the effect of application of Pender's HPM on management of hypertension among adults in rural area [18], examined the impact of performing a HPM intervention on physical activity of the health Volunteers [19], and investigated the effect of Pender's HPM to improve the nutritional behavior of overweight and obese women admitted to Fatemiyeh…”
Section: The Purposes Of the Reviewed Studiesmentioning
confidence: 99%
“…The second category is the studies that tested a samples and populations of chronic illness. The samples were 75 patients with a clinical diagnosis of osteoporosis and 75 patients with osteoarthritis [8], 190 patients with ESRD receiving hemodialysis [9], 190 patients with ESRD [11], 402 outpatient with chronic illnesses [14], 272 patients with chronic illness [16], and 150 adults with hypertension [18].…”
Section: Sample Of Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26] In addition, a previous study conducted in Jordan found that the modified ESE demonstrated high validity and internal consistency for use in an Arabic-speaking population, based on factor analysis and internal consistency reliability tests. 27 The main interest in the current study was to examine SE related to the ability to perform PA in the face of previously identified barriers to PA. 17 As such, two questions in the ESE scale were modified to highlight these barriers, namely: "How confident are you that you can engage in physical activity when you do not have access to PA resources?" and "How confident are you to overcome lack of social support that could be an obstacle to performing PA?".…”
Section: Methodsmentioning
confidence: 99%